2011
DOI: 10.4028/www.scientific.net/amr.291-294.167
|View full text |Cite
|
Sign up to set email alerts
|

TiC Particle Reinforced Reactive Plasma Cladding Composite Coating by the Precursor Carbonization-Composition Process

Abstract: Fe-Cr-Ti-C composite powder was prepared by precursor carbonization-composition process using the mixture of ferrotitanium, chromium, iron powders and precursor sucrose as raw materials. In situ synthesized TiC particle reinforced composite coating was fabricated on substrate of Q235 steel by reactive plasma cladding process using Fe-Cr-Ti-C composite powder. Microstructure of the coating was observed by scanning electron microscope (SEM), the phases in the coating were determined by X-ray diffraction (XRD), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Because of its high hardness and wear resistance, Fe-Cr-C-Ti alloy has been widely applied in metallurgical, mineral and cement industries [1][2][3]. According to its microstructure, the Fe-Cr-C-Ti alloy can be divided into hypoeutectic, eutectic and hypereutectic ones, and the microstructure is mainly composed of martensite and complex carbides, such as MC, M 7 C 3 and M 23 C 6 [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Because of its high hardness and wear resistance, Fe-Cr-C-Ti alloy has been widely applied in metallurgical, mineral and cement industries [1][2][3]. According to its microstructure, the Fe-Cr-C-Ti alloy can be divided into hypoeutectic, eutectic and hypereutectic ones, and the microstructure is mainly composed of martensite and complex carbides, such as MC, M 7 C 3 and M 23 C 6 [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Laser equipment costs 4-5 times as much as plasma equipment. Studies have been shown that the production efficiency of plasma cladding is about 6-10 times of laser cladding, and the powder utilization ratio of plasma cladding is about 2-4 times that of laser cladding [9][10][11]. Therefore, plasma cladding technology has broad application prospects in many fields such as machinery, electric power, coal and metallurgy.…”
Section: Introductionmentioning
confidence: 99%